Revisiting the linkage between green finance and China’s sustainable development: evidence from the pilot zones for green finance reform innovations - Lin, Guochao; Lam, Johnny F. I.; Shi, Yi; Chen, Hongxi; Chen, Huangxin (Frontiers in Ecology and Evolution, 2023)
Based on the fundamental logic of 'green finance -improvement of ecological environment and new kinetic energy of economic development -sustainable development of economy and society', this paper conducts quasi-natural experiments using panel data from 30 provinces and cities in China between 2013 and 2021. It explores the effects of pilot policies of the green finance reform and innovation pilot zone on the sustainable development of the economy and society through a double difference model. The study reveals that the establishment of the green finance reform and innovation pilot zone has a significant promoting effect on the sustainable development of the economy and society. This conclusion remains valid even after conducting a series of robustness tests. In further analysis, it is found that the promotion effect of the green finance reform and innovation pilot zone on sustainable development exhibits some temporal characteristics. It is particularly significant in regions with lower levels of financial development and industrialization but higher levels of technological innovation. Mechanism analysis indicates that the pathways through which the green finance reform and innovation pilot zone facilitates economic and social sustainable development are relatively singular, primarily revolving around the improvement of the ecological environment. The key contribution of this paper lies in demonstrating the crucial role of pilot policies in the field of sustainable economic and social development.Additionally, it offers new insights for strengthening the implementation effectiveness of green finance pilot policies.